2012
DOI: 10.1002/prep.201100161
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Porphyrin Doping on Thermodynamic Parameters of Pentaerythritol Tetranitrate (PETN) Single Crystals

Abstract: The search for ways to enhance the stability of PETN against sublimation and coarsening, as well as controlling its thermodynamic properties, is of great interest. In this article, the possibility to use biological molecules to enhance the stability of the important explosive PETN was investigated using thermogravemitric analysis (TGA). Doping PETN with free and metallated porphyrins result in the formation of more stable crystals. Hydrogen bonding between free porphyrins and metal coordination of metallated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Keywords: Single crystal · PETN · Doping · Impurities · Mass-Loss rate · Morphology ous works have demonstrated that doping with appropriate compounds can control such aging process of PETN [11,17,18]. For instance, it was shown that doping with homologs like dipentaerythritol hexanitrate (diPEHN) and tripentaerythritol octanitrate (triPEON) can lower the vapor pressure of PETN single crystals [19].…”
Section: Introductionmentioning
confidence: 99%
“…Keywords: Single crystal · PETN · Doping · Impurities · Mass-Loss rate · Morphology ous works have demonstrated that doping with appropriate compounds can control such aging process of PETN [11,17,18]. For instance, it was shown that doping with homologs like dipentaerythritol hexanitrate (diPEHN) and tripentaerythritol octanitrate (triPEON) can lower the vapor pressure of PETN single crystals [19].…”
Section: Introductionmentioning
confidence: 99%
“…This is followed by reaction with another equivalent of DNT to give the hydroxylated catalyst 16 and dehydroxylation eventually restores 10 184. The thermodynamic stability of 2,2-bis[(nitrooxy)methyl]propane-1,3-diyl dinitrate (PETN), another explosive with high brisance that was used, for example, in the 1980 Paris synagogue bombing, was enhanced via doping with an iron porphyrin 189. This is an early step towards the use of porphyrins to enhance the stability of energetic materials for safe use and IED disposal.…”
mentioning
confidence: 99%